Nghiên cứu chế tạo sơn nước trên cơ sở nhựa epoxy biến tính bằng dầu vỏ hạt điều - Cúc, Huỳnh Thị (Vietnam Journal of Chemistry, 2012)
Cashew Nut Shell Liquid (CNSL) has principal chemical compositions as cardanol, cardol, 2-methyl cardol,… So it has property like both phenols and drying oils. Its epoxidation by peracetic acid at temperature from 50oC to 75oC was studied.  The obtained results showed that at the molar ratio of the hydroperoxyd and double bonds of CNSL, the reaction temperature 60 – 65oC was optimal to maximize the epoxidized CNSL yield. Emulsifying it with hydropalate 5040 will receive the water- borne coating, be friendly with environment, initially meet the demand to TCVN 6394:2001. This result increases the value-added of CNSL, simultaneously contributes the new product line and raises the competitive capability for the paint-material industry in Vietnam.